Perspectives of Pulmonologists on the 2009-2010 H1N1 Vaccination Effort - Sarah J. Clark; Anne E. Cowan; Pascale M. Wortley (Pulmonary Medicine)
Persons with high-risk conditions such as asthma were a target group for H1N1 vaccine recommendations. We conducted a mailed survey of a national sample of pulmonologists to understand their participation in the 2009-2010 H1N1 vaccine campaign. The response rate was 59%. The majority of pulmonologists strongly recommended H1N1 vaccine for children (73%) and adults aged 25–64 years (51%). Only 60% of respondents administered H1N1 vaccine in their practice compared to 87% who offered seasonal influenza vaccine. Other than vaccine supply, respondents who provided H1N1 vaccine reported few logistical problems. Two-thirds of respondents would be very likely to vaccinate during a future influenza pandemic; this rate was higher among those who provided H1N1 vaccine and/or seasonal flu vaccine. In total, the H1N1 vaccine-related experiences of pulmonologists seemed to be positive. However, additional efforts are needed to increase participation in future pandemic vaccination campaigns.